2022
DOI: 10.3390/en15207712
|View full text |Cite
|
Sign up to set email alerts
|

Induction Motor Supplied with Voltage Containing Symmetrical Subharmonics and Interharmonics

Abstract: Sinusoidal voltage fluctuations can be considered a specific result of the occurrence of voltage subharmonics and interharmonics, which are components of low frequency or not being an integer multiple of the frequency of the fundamental voltage harmonic. These components—symmetrical subharmonics and interharmonics—are of the same magnitude, while their frequencies are symmetrical with respect to the fundamental frequency. Depending on their phase angles, various kinds of voltage fluctuations can be distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 40 publications
2
25
1
Order By: Relevance
“…In addition, previous research [5,[35][36][37][38] indicated high transverse vibration of the rotating machinery for no-load, while in other load conditions, the observed vibration was generally moderate. At the same time, at least temporarily, many motors carry a load much less than rated [42,43], but this is not typical.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…In addition, previous research [5,[35][36][37][38] indicated high transverse vibration of the rotating machinery for no-load, while in other load conditions, the observed vibration was generally moderate. At the same time, at least temporarily, many motors carry a load much less than rated [42,43], but this is not typical.…”
Section: Introductionmentioning
confidence: 91%
“…A prominent source of SaIs includes time-varying loads, which can be divided into regularly fluctuating loads, e.g., welder machines, laser printers, and devices with integral cycle control, and irregularly fluctuating loads, such as arc furnaces [16]. The work of timevarying loads causes current modulation [7,16], resulting in voltage fluctuations [7,25,26,35]. At the same time, sinusoidal voltage fluctuations can be analysed as a superposition of the fundamental voltage component, a subharmonic component, and an interharmonic component of the following frequencies [7,27,31,35]:…”
Section: Origin Of Voltage Subharmonics and Interharmonicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disturbances in the power quality have negative impacts on particular elements of the power system, including electric machines [ 2 , 3 ], causing, e.g., their overheating [ 4 ], excessive vibrations [ 5 ], torsional vibrations [ 6 ], reduced efficiency [ 7 ], loss of reliability, and durability [ 8 , 9 , 10 ]. Power quality disturbances that occur in the power grid and affect the reliability of electrical machines include, among others, voltage fluctuations [ 11 , 12 ], voltage distortions caused by higher harmonics [ 13 ] or inter-harmonics [ 14 , 15 ]. At the same time, in some cases, the operation of electric machines or devices associated with them can also cause disturbances of power quality [ 16 , 17 , 18 ], for example, the electric machine control or the charging of an electric vehicle (EV) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%